A New Technique for Posterior Distraction in Craniosynostosis: The Double-Door Technique. Issue 4 (June 2016) - Sakamoto, Yoshiaki; Miwa, Tomoru; Nakajima, Hideo; Yoshida, Kazunari; Kishi, Kazuo
Abstract : Background: Posterior cranial vault distraction osteogenesis is a common treatment for syndromal patients of brachycephaly and oxycephaly. Although posterior distraction can increase intracranial volume, the flattened head phenotype is difficult to correct. The authors examined a new posterior distraction technique termed double-door distraction for improvement of the flattened head phenotype. Methods: From 2010 to 2013, 6 patients with flattened posterior craniums were operated on using the double-door distraction technique. The calvarial segment was cut at the midline and divided into 2 pieces. Distractors were then fixed in parallel to join the calvarial pieces. The distraction was initiated at a rate of 1.0 mm/day and continued until proper cranial form was confirmed by radiography and appearance. Results: The average surgery time was 2 hours 47 minutes and the amount of distraction ranged from 15 to 22 mm. An improved head shape and expanded cranial vault was achieved in all patients without any complications. Conclusions: The double-door distraction technique is a useful technique not only for calvarial expansion, but also for correction of the flattened posterior cranium phenotype.